Fractal dimensional analysis on dispersion/aggregation state of MWCNT in poly(4-chloromethyl)styrene: effect of UV-induced polymer-MWCNT chemical bond formation and its influence on electrical conductivity of their composites. Issue 4 (18th May 2020) - Takada, Tomoya; Ushiromura, Ryoga; Fushiki, Takuto
Abstract: The effects of ultraviolet (UV)-induced chemical bond formation on the dispersion/aggregation state of multi-walled carbon nanotubes (MWCNTs) in poly(4-chloromethyl)styrene/MWCNT composites and their electrical conductivity were examined using transmission electron microscopy (TEM) and fractal dimensional analysis of the TEM images. The composites prepared with UV irradiation exhibited lower electrical conductivity and denser aggregation of the trapped MWCNTs than those observed for unirradiated composites. Fractal dimensional analysis of the TEM images indicated that the difference in the dispersion/aggregation state associated with electrical conductivity could be correlated to the fractal dimension calculated by the box-counting method.